Potential New Approaches for Prostate Cancer Management in Resource-Limited Countries in Africa - Maarten C. Bosland; Olayiwola B. Shittu; Edet E. Ikpi; Oluyemi Akinloye (Ubiquity Press, 2023)
Prostate cancer is a major male malignancy in many sub-Saharan countries in Africa. Because of resource limitations, screening, early detection, diagnosis, and curative treatments are not available for many men on the subcontinent, and there are even barriers to the treatment of advanced-stage metastatic prostate cancer. We are making the case for new approaches to the detection, diagnosis, and treatment of this malignancy in sub-Saharan Africa and other low-resource regions-approaches that differ from the ones available and used in high-income countries. The development of one-step dipstick-type detection assays of serum prostate-specific antigen (PSA) offers an approach to prostate cancer detection, treatment and monitoring that circumvents issues related to laboratory quality control and is also low-cost. Curative-intent treatments of early-stage prostate cancer are often unavailable in low-resource contexts, and most prostate cancers are not detected in Africa until they are at an advanced stage. Hence, androgen deprivation treatments, including orchiectomy and older low-cost drugs, offer feasible and affordable approaches to prolong survival and sustain a reasonable quality of life. However, clinical trials are needed to identify which of these androgen deprivation treatments are most efficacious and best tolerated to make progress in providing medical care for men with prostate cancer in sub-Saharan Africa and other low- and lower-middle-income areas around the world.